Analisis Semantik Konsep Rezeki dalam Tafsir Al-Misbah dan Implikasinya dalam Konteks Kognitif dan Etis - Raudatul Aliyah Lubis; Indra Suardi; Nurdiani (Journal of Islamic Scriptures in Non-Arabic Societies, 2024)
This study examines Quraish Shihab’s interpretation of the concept of rizq in Tafsir al-Misbah through the lens of Jean Piaget’s cognitive development theory and Lev Vygotsky’s socio-cognitive theory. The academic problem addressed is how the concept of rizq, involving effort, prayer, and social interaction, can be understood from the perspective of cognitive development and social ethics. The study aims to fill the gap in tafsir analysis by incorporating psychological approaches, particularly in understanding how theological thoughts on rizq influence cognitive development and the formation of individual ethics. The research method used is textual analysis of Tafsir al-Misbah with theoretical approaches from Piaget and Vygotsky, exploring both cognitive and ethical aspects in the process of acquiring rizq. The novelty of this research lies in applying psychological developmental theories to tafsir analysis, a rarely undertaken approach in Quranic exegesis studies. The results indicate that Quraish Shihab's interpretation of rizq encompasses cognitive aspects that encourage logical and abstract thinking about effort and prayer, as well as ethical aspects that emphasize social responsibility and integrity in the pursuit of sustenance. This tafsir promotes the development of a proactive mindset and a strong ethical awareness through social interaction within the community.